Financial Inclusion dan Stabilitas Perbankan: Bukti Empiris Bank yang Terdaftar di BEI - Rachmawati Rachmawati; Belliwati Kosim; Mister Candera (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
To determine the effect of financial inclusion based on the number of savings accounts, the number of ATM machines, and the number of deposit accounts on bank stability in banking sector companies listed on the Indonesia Stock Exchange The data used is secondary data, with data collection techniques using the documentation method. The sample in this study used the purposive sampling method, namely 19 banking sector companies listed on the IDX in 2019-2023. The quantitative analysis technique uses a multiple linear regression model using SPSS Version26.The results of this study indicate that 1) There is a significant influence of financial inclusion simultaneously on bank stability 2) There is an influence of financial inclusion based on savings accounts partially on bank stability 3) There is an influence of financial inclusion based on the number of ATM machines partially on bank stability 4) There is an influence of financial inclusion based on the number of deposit accounts partially on bank stability in banking sector companies listed on the Indonesia Stock Exchange in 2019-2023. The limitations of this study are only banking sector companies listed on the IDX in 2019-2023. This study only covers 19 companies from the banking sector listed on the Indonesia Stock Exchange. This sample only represents 40.4% of the population of companies in the banking sector. Several companies do not meet the criteria because they do not consistently publish and present complete financial reports, so the number of samples used in this study is limited. This research can be used as a consideration for the Company in formulating the Company's strategy to be taken. To improve access to financial services for people in the lower classes through the resilience of the banking funding base. This research update introduces a new method in data analysis using SPSS version 26 and banking data for 2019-2023.